Restoration of Deprived Clergy during the 1559 Royal Visitation of the Eastern Dioceses - Houlbrooke, Ralph (Studies in church history, 2020)
It is well known that many of the English clergy took advantage of the statutory authorization of clerical marriage under Edward VI, but then suffered deprivation when that authorization was rescinded in Mary's reign. Less familiar are the proceedings that enabled incumbents who had lost their livings as a penalty for marriage to recover them after Elizabeth I's accession. This article focuses on a neglected source, an act book kept during the royal visitation of the eastern dioceses (London, Norwich and Ely) in 1559. It seems likely that this document records a large majority of the suits undertaken by deprived married clergy for the recovery of their livings in those dioceses. Most claimants were successful, but some suits failed, for a variety of reasons. Other sources, and the work of previous scholars in the field, shed some light on the recovery of their livings by men who do not appear in the act book. Probably rather more than a quarter of the men deprived for marriage under Mary in these dioceses recovered their livings in or after 1559. Many others had died or for various reasons did not seek restoration to the benefices of which they had been deprived.